Combined Strategy Using High Hydrostatic Pressure, Temperature and Enzymatic Hydrolysis for Development of Fibre-Rich Ingredients from Oat and Wheat By-Products - Iván Jesús Jiménez-Pulido; Daniel Rico; Daniel De Luis; Ana Belén Martín-Diana (Foods, 2024)
Wheat bran (WB) and oat hull (OH) are two interesting undervalued cereal processing sources rich in total dietary fibre (TDF) and other associated bioactive compounds, such as β-glucans and polyphenols. The aim of this study was to optimise a combination chemical (enzymes) and physical (high hydrostatic pressure-temperature) strategies to increase the bioaccessibility of bioactive compounds naturally bound to the bran and hull outer layers. WB and OH were hydrolysed using food-grade enzymes (UltraFloXL and Viscoferm, for WB and OH, respectively) in combination with HPP at different temperatures (40, 50, 60 and 70 °C) and hydrolysis either before or after HPP. Proximal composition, phytic acid, β-glucans, total phenolics (TPs) and total antioxidant activity (TAC) were evaluated to select the processing conditions for optimal nutritional and bioactive properties of the final ingredients. The application of the hydrolysis step after the HPP treatment resulted in lower phytic acid levels in both matrices (WB and OH). On the other hand, the release of β-glucan was more effective at the highest temperature (70 °C) used during pressurisation. After the treatment, the TP content ranged from 756.47 to 1395.27 µmol GAE 100 g−1 in WB, and OH showed values from 566.91 to 930.45 µmol GAE 100 g−1. An interaction effect between the temperature and hydrolysis timing (applied before or after HPP) was observed in the case of OH. Hydrolysis applied before HPP was more efficient in releasing OH TPs at lower HPP temperatures (40–50 °C); meanwhile, at higher HPP temperatures (60–70 °C), hydrolysis yielded higher TP values when applied after HPP. This effect was not observed in WB, where the hydrolysis was more effective before HPP. The TP results were significantly correlated with the TAC values. The results showed that the application of optimal process conditions (hydrolysis before HPP at 60 or 70 °C for WB; hydrolysis after HPP at 70 °C for OH) can increase the biological value of the final ingredients obtained.